Predicting Maximal Lactate Steady State from Carminatti’s Shuttle Run Test in Soccer Players - Carminatti, Lorival José; Batista, Bruna Nunes; da Silva, Juliano Fernandes; Tramontin, Artur Ferreira; Costa, Vitor Pereira; de Lucas, Ricardo Dantas; Borszcz, Fernando Klitzke (International Journal of Sports Medicine, 2020)
The objective of the present study was to determine the validity of Carminatti’s shuttle run incremental test–T-Car derived parameters in estimating the maximal lactate steady state determined in shuttle run format. Eighteen soccer players performed a T-Car test, and several trials to determine the maximal lactate steady state. From T-Car were derived the heart rate deflection point, peak speed, maximal heart rate and parameters resulting from percentage of peak measures. The validity was accessed by Bland-Altman plots, linear regressions, and two one-sided tests of equivalence analysis. The results showed the speed at 80.4% of T-Car peak speed, the heart rate deflection point and the 91.4% of maximal heart rate were equivalent to maximal lactate steady state (Mean difference; ±90% compatibility interval; −0.8; ±1.5%, −0.4; ±1.1%, and 0.0; ±2.7%, respectively). Additionally, peak speed during the T-Car test was a stronger predictor of maximal lactate steady state (MLSS [km/h]=2.57+0.65 × sPeak; r=0.82 [90% CI; 0.62–0.92], standard error of the estimate=3.6%; 90% CI ×/÷1.4). Therefore, soccer players can use the T-Car derived parameters as a noninvasive and practical alternative to estimate the specific maximal lactate steady state for soccer.
Keywords: validity; soccer; field test